1995
DOI: 10.1063/1.871264
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the simulation of toroidal gyro-Landau fluid model turbulence

Abstract: The gyro-Landau fluid (GLF) model equations for toroidal geometry [R.E. Waltz, R.R. Dominguez, and G.W. Hammett, Phys. Fluids B 4, (1992) 3 1381 have been recently applied to the study ion temperature gradient (ITG) mode turbulence using the 3D nonlinear ballooning mode representation (BMR) outlined in [R.E. Waltz, G.D. Kerbel, and J. Milovich, Phys. Plasmas 1, 2229 (1994)l. The present paper extends this work by treating some unresolved issues concerning ITG turbulence with adiabatic electrons. Although eddie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
159
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(173 citation statements)
references
References 10 publications
13
159
1
Order By: Relevance
“…It is adjusted to be narrow during ramp up and broadened for H-mode conditions at high auxiliary power input. The temperature profiles are determined from the assumed transport model, typically used is GLF23 [9] without rotation over most of the profile and the edge (where GLF23 is known not to be valid) by a scaled L-mode [10] model. The overall minimum thermal conductivity is set to neoclassical values.…”
Section: Scenario Control Evaluation (Sce) Modementioning
confidence: 99%
“…It is adjusted to be narrow during ramp up and broadened for H-mode conditions at high auxiliary power input. The temperature profiles are determined from the assumed transport model, typically used is GLF23 [9] without rotation over most of the profile and the edge (where GLF23 is known not to be valid) by a scaled L-mode [10] model. The overall minimum thermal conductivity is set to neoclassical values.…”
Section: Scenario Control Evaluation (Sce) Modementioning
confidence: 99%
“…The uncertainties in the fitting coefficients (listed in the caption of figure 13) are large because the small amount of data and the size of the measurement uncertainties limits the capability to separate the scaling with the pressure profile shape from the scaling with q core and q 95 . In addition, discharge-to-discharge differences in the details of the pressure profile shape are not included in equation (4). An F-test [36] showed that each of the fitting coefficients improves the fit by a statistically significant amount.…”
Section: Scaling Of F Bsmentioning
confidence: 99%
“…Conversely, the q profile is strongly dependent on J BS when f BS is large, and in a steady-state tokamak, f BS must be large in order to minimize the required external current drive power [3]. The temperature and density gradients depend on the transport coefficients, which also depend on q as well as the magnetic shear [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…37 Hence, important open qualitative questions remain, even before the quantitative ones can be addressed about the detailed dependence of both e and ˙e on s and q: Does the increased negative central shear affect the barrier at s = 0 indirectly through a modification of its gradient sЈ there, or does it act to reduce the local energy diffusivity? [38][39][40] In the latter case, does the dynamical evolution ͑˙e͒ depend on s, resulting in a delayed but ultimately efficient diffusivity quench in the center? If the barrier instead does remain localized at s = 0, as advocated by the so-called radial-gap or zero-shear-gap theories, 41 what parameters govern its width?…”
Section: -5mentioning
confidence: 99%